Effect of Co-fermentation with Streptococcus salivarius subsp. thermophilus and Bifidobacterium animalis subsp. lactis on Improving the Quality of Fermented Milk - LIU Zhizhong, LIU Liwei, LIU Zhigang, CHEN Haili, CUI Hong, YANG Bo, ZHANG Jiaqi, WU Rigeng, YAO Kai (Shipin Kexue)
This study evaluated the effect of co-fermentation using Streptococcus salivarius subsp. thermophilus CZ-03 and Bifidobacterium animalis subsp. lactis LGG-08 on the quality of fermented milk. Changes in microrheological properties during the fermentation process were studied using multi-frequency diffusing wave spectroscopy, and changes in pH, titratable acidity (TA), viable bacterial count (VBC), exopolysaccharide (EPS) content, viscosity, water-holding capacity (WHC), texture properties, and sensory evaluation were examined as well. The results showed that during the initial storage period (0–14 days), the EPS content of the co-fermented milk increased from 204.7 to 233 mg/L, which was significantly higher than that of the single-strain fermented milk. Additionally, the VBC in the co-fermented milk was significantly higher than that in the single-strain fermented milk throughout the storage period, indicating that the co-fermentation could significantly enhance the storage stability and probiotic functions of the product. The use of co-cultures markedly improved the rheological and texture characteristics of fermented milk, particularly viscosity and WHC. Compared with the single-strain fermented milk, the co-fermented milk was more capable of forming a stable gel structure. These findings provide a solid scientific basis for the development of probiotic fermented milk products and the enhancement of their health benefits and also offer innovative perspectives and strategies for the production and storage characteristics evaluation of fermented milk.